Ibnu Khaldun and Adam Smith: A Comparative Analysis of Economic Growth and State Role - Rahmatullah, M. Riki; Ubaidillah (Research Horizon, 2025)
This study aims to compare the economic thought of Ibnu Khaldun and Adam Smith in relation to economic growth and the role of the state. Both thinkers, emerging from different historical and cultural contexts Ibnu Khaldun from 14th century Islamic civilization and Adam Smith from 18th-century Western classical economics offer foundational ideas on how economies develop and the function of governance. Using a qualitative approach with literature study as the method, this research analyzes the key similarities and differences in their views. The findings reveal that while Adam Smith is often associated with the laissez-faire principle, he acknowledges the necessity of state involvement in providing public goods and maintaining legal frameworks. Conversely, Ibnu Khaldun views a just and stable government as essential for sustaining economic prosperity, emphasizing moral and political stability. The study highlights that both thinkers recognize the interplay between governance and economic development. These insights contribute to enriching modern economic discourse by integrating historical and ethical perspectives, offering a more holistic foundation for addressing current economic challenges and rethinking the role of the state in ensuring sustainable growth.